Manager gender, entrepreneurial orientation and SMEs export and import propensities: evidence for Spanish businesses - Expósito-García, Alfonso; Sanchis-Llopis, Amparo; Sanchis-Llopis, Juan Alberto (Springer, 2022)
This paper investigates the role of manager gender in SMEs’ decisions to get involved in exporting and importing activities, using a sample of 1,405 Spanish SMEs. We borrow insights from international entrepreneurship theories and feminist theories to set testable hypotheses regarding how managerial gender and entrepreneurial orientation (proactiveness, risk-taking and innovativeness) may influence SMEs export and import propensities. Using a bivariate probit model and controlling for other managerial and business characteristics, results reveal that there are not significant disparities in exporting propensities between men- and women-run businesses. However, female-led SMEs show a lower importing propensity, in comparison to male-led counterparts. In addition, the three entrepreneurial orientation dimensions (proactiveness, risk-taking and innovativeness) are important drivers for participating in overseas markets, and do not depend upon the manager gender. This work provides new empirical evidence on the comparison between men- and women-run SMEs as regards export/import behavior and thus, it contributes to improve our knowledge on the role of gender in SMEs internationalization. The role of manager’s gender in SMEs import propensity has not been investigated so far, and this is the main novelty of our research.
Keywords: Empresas - Gestión; Manager gender; Entrepreneurial orientation; Small and mediumenterprises; Exporting and importing